2018
DOI: 10.1137/18m1171060
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Eisenberg--Noe Clearing Vector to Individual Interbank Liabilities

Abstract: We quantify the sensitivity of the Eisenberg-Noe clearing vector to estimation errors in the bilateral liabilities of a financial system. The interbank liabilities matrix is a crucial input to the computation of the clearing vector. However, in practice central bankers and regulators must often estimate this matrix because complete information on bilateral liabilities is rarely available. As a result, the clearing vector may suffer from estimation errors in the liabilities matrix. We quantify the clearing vect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 63 publications
(80 reference statements)
0
24
0
Order By: Relevance
“…They considered an environment, in which all participants (henceforth, "banks") default within a single clearing mechanism, and demonstrated that there always exist a "clearing payment vector" that satisfy some natural requirements. The Eisenberg-Noe approach has been successfully extended to incorporate liquidity spillovers (Cifuentes, Ferrucci and Shin, 2005;Shin, 2008), outside liabilities (Elsinger, 2009;Glasserman and Young, 2015), costs of default (Rogers and Veraart, 2013), liabilities of different seniority (Kusnetsov and Veraart, 2019), mandatory disclosures (Alvarez and Barlevy, 2015), and other financial instruments, and has become a cornerstone in analysis of systemic financial risk (see, e.g., Hurd, 2016;Feinstein et al, 2018;Kabanov, Mokbel and El Bitar, 2018, for recent surveys).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They considered an environment, in which all participants (henceforth, "banks") default within a single clearing mechanism, and demonstrated that there always exist a "clearing payment vector" that satisfy some natural requirements. The Eisenberg-Noe approach has been successfully extended to incorporate liquidity spillovers (Cifuentes, Ferrucci and Shin, 2005;Shin, 2008), outside liabilities (Elsinger, 2009;Glasserman and Young, 2015), costs of default (Rogers and Veraart, 2013), liabilities of different seniority (Kusnetsov and Veraart, 2019), mandatory disclosures (Alvarez and Barlevy, 2015), and other financial instruments, and has become a cornerstone in analysis of systemic financial risk (see, e.g., Hurd, 2016;Feinstein et al, 2018;Kabanov, Mokbel and El Bitar, 2018, for recent surveys).…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Staum (2010) provided a formula for sensitivity analysis of Eisenberg and Noe's one-period model of contagion via direct bilateral links. Feinstein et al (2018) quantified the Eisenberg-Noe clearing vector's sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cifuentes, Ferrucci & Shin (2005) allow for liquidity considerations and Rogers & Veraart (2013) introduce costs of default. More recently, Feinstein, Pang, Rudloff, Schaanning, Sturm & Wildman (2018) test the sensitivity of the Eisenberg-Noe clearing vector to estimation errors in bilateral interbank liabilities. There are also studies on alternative clearing processes.…”
Section: Related Literaturementioning
confidence: 99%
“…Often, even regulators have only a partial view of the detailed structure of interbank assets. Indeed, a separate strand of literature is focused specifically on trying to "reconstruct" interbank assets from publicly available information (Anand, Craig, & Von Peter, 2015;Cimini, Squartini, Garlaschelli, & Gabrielli, 2015;Gandy & Veraart, 2016;Squartini, Cimini, Gabrielli, & Garlaschelli, 2017;Squartini, Caldarelli, Cimini, Gabrielli, & Garlaschelli, 2018) or to assess the impact of their misestimation (Feinstein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%